2002
DOI: 10.1128/iai.70.3.1097-1105.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Pulsed with a Recombinant Chlamydial Major Outer Membrane Protein Antigen Elicit a CD4+Type 2 Rather than Type 1 Immune Response That Is Not Protective

Abstract: Chlamydia trachomatis is an obligate intracellular bacterium that infects the oculogenital mucosae. C. trachomatis infection of the eye causes trachoma, the leading cause of preventable blindness. Infections of the genital mucosae are a leading cause of sexually transmitted diseases. A vaccine to prevent chlamydial infection is needed but has proven difficult to produce by using conventional vaccination approaches. Potent immunity to vaginal rechallenge in a murine model of chlamydial genital infection has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 46 publications
(30 reference statements)
3
57
0
Order By: Relevance
“…Recently Shaw et al (29) reported that DCs pulsed with chlamydial major outer membrane protein or UVEB induced Ag-specific CD4 T cell proliferation in vitro, but that only immunization with DCs pulsed with UVEB induced Th1-mediated protective immunity in vivo. Immunization with DCs pulsed with major outer membrane protein elicited Th2 immune responses without significant protection against challenge infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Shaw et al (29) reported that DCs pulsed with chlamydial major outer membrane protein or UVEB induced Ag-specific CD4 T cell proliferation in vitro, but that only immunization with DCs pulsed with UVEB induced Th1-mediated protective immunity in vivo. Immunization with DCs pulsed with major outer membrane protein elicited Th2 immune responses without significant protection against challenge infection.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization with DCs pulsed with major outer membrane protein elicited Th2 immune responses without significant protection against challenge infection. The authors suggested that the nature of the Ag used to pulse DCs may influence the maturation of DCs and thereby skew the Th1-Th2 balance of the immune response in vivo (29). In the absence of maturation, Agloaded DCs may induce Ag-specific tolerance or polarize the immune response to a type 2 pattern (30).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Su et al (37) and Shaw et al (38) have reported that adoptive transfer of whole Chlamydia organism-pulsed bone marrowderived DC induce strong Th1 responses and protection to challenge infection, while major outer membrane protein (MOMP)-pulsed bone marrow-derived DC induce Th2-type responses and failed to provide protection (48). In addition, these authors also found that the DC pulsed with whole chlamydial organism produce higher IL-12 than the DC pulsed with MOMP.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the wealth of literature examining the ability of ex vivo-primed DCs to sensitize against infectious diseases (3)(4)(5)(6)(7) and also the mechanisms that DCs initiate to prime immunity, there is little understanding of the role of DCs during intestinal nematode infection. It is clear that a Th2 immune response, characterized by the secretion of IL-4, IL-9, and IL-13 (8 -11), leads to complete expulsion of adult worms from the intestine, although the role of DCs in the induction of this response remains to be precisely determined.…”
Section: Induction Of Enhanced Immunity To Intestinal Nematodesmentioning
confidence: 99%